Dakwah Islam di Era Disrupsi - Mardiana Mardiana (Alhadharah: Jurnal Ilmu Dakwah, 2020)
Da'wah represents every Muslim, male, or female. The basis of this preaching law is adjusted to the skills and understanding and understanding of religion supported by someone. One of the supporting elements of the success of Islamic da'wah is the media. The use of media certainly adapts to the conditions of mad'u. The more developed the community, the more modern the media coverage. This is marked by the shifting of their daily habits to the use of social media. The intensity of the use of social media is mostly the general public and Muslims in particular. Digitalization cannot be released by Muslims in this era of disruption, especially in the world of da'wah. The preachers and mad'u must work together to preach Islam so that the success of preaching can be obtained according to the target.